ORGANIK MATERIAL REMOVAL MODELLING FOR ADDITION OF ARTIFICIAL SUPPORT MATERIAL AS A TREATMENT FOR WATER BODY - Shani Fathuna, Inat
The significant increase in population causes the needs to be fulfilled are increasing. The increasing need means that the amount of waste produced will also increase which can pollute water bodies. Additional treatment is required to reduce the pollutant load received by water bodies. The addition of supporting media is an additional treatment to reduce pollutant loads in water bodies. In previous studies, the use of drainblocks as a supporting media in water bodies both on a laboratory and field scale showed satisfactory results in removing organik pollutants. This study aims to model the removal of organik pollutants represented by the COD value to determine the drainblock dimensions that need to be applied to other cases. The data used in this study are field scale data using two types of drainblocks, namely drainage and water retention drainblock (type I) and water treatment drainblock (type II). There are form variations of drainblock namely cubes and blocks. In total, there are four variations of the drainblocks application, as follows type I drainblock-block form, type I drainblock-cube form, type II drainblock-cube form, and type II drainblock-block form. The method used is to put the field data into the reaction kinetics equation of zero order, first order, and second order obtained from the derivation of the plug flow reactor equation. A comparison of the standard deviation and the coefficient of determination is used to determine the reaction kinetics equation used, the reaction coefficient value, and the optimal supporting media application. The modeling results show that the most optimal type of drainblock to remove COD is type II drainblock-cube form using the first order kinetics equation. The reaction coefficient (k) obtained is 0,5378/s, standard deviation value is 14,532 mg/L COD, and the coefficient of determination is 0,1025. The kinetics value of the reaction removal and equations obtained are used to make modeling in Matlab R2020b application to determine the dimensions of the drainblock required to remove pollutants.